EKSISTENSI BARONG DAN RANGDA (EKSPLORASI TEOLOGI HINDU) - Susandi, I Made Ari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The dynamics of Balinese people's lives are constantly under the spotlight because of the variety of cultural activities that blend with various lives. The arts of barong and rangda are spread across all districts and cities in Bali, but not all pakraman villages or temples have barong and rangda arts. This is due to the existence of barong and rangda in the religious dynamics of Balinese Hindu society. although in reality barong and rangda are not merely an art form, but furthermore they are the implementation of theology (divine teachings) of Hinduism, both concerning the philosophical (essential) religious side and religious psychology (psychological/emotional aspect).